Microorganisms associated with the North African hedgehog Atelerix algirus and its parasitizing arthropods in Algeria. (January 2022) - Aouadi, Nawal; Benkacimi, Linda; Zan Diarra, Adama; Laroche, Maureen; Bérenger, Jean-Michel; Bitam, Idir; Parola, Philippe
Abstract: Hedgehogs are small mammals. They are potential reservoirs of various zoonotic agents. This study was conducted in Bouira, a north-central region of Algeria. A total of 21 Atelerix algirus corpses were picked up on roadsides and gardens. Hedgehog kidneys, spleens and ectoparasites were collected. Twelve hedgehogs were infested with ectoparasites, including Archaeopsylla erinacei, Rhipicephalus sanguineus s.l. and Haemaphysalis erinacei . Hedgehog organs and randomly selected arthropods were screened for microorganisms using molecular methods. Coxiella burnetii was detected in kidneys, spleens, A. erinacei, Hae. erinacei and Rh. sanguineus s.l. Leptospira interrogans was detected in kidneys. Rickettsia felis and Rickettsia massiliae were detected respectively in A. erinacei and in Rh. sanguineus s.l. DNA of an uncultivated Rickettsia spp. was found in Hae. erinacei . Wolbachia spp. DNA was detected in fleas. The DNA of potential new Bartonella and Ehrlichia species were found respectively in fleas and ticks. This study highlights the presence of DNA from a broad range of microorganisms in hedgehogs and their ectoparasites that may be responsible for zoonoses in Algeria. Graphical Abstract: ga1 Highlights: Atelerix algirus hedgehogs were infested by Archaeopsylla erinacei, Haemaphysalis erinacei and Rhipicephalus sanguineus . Detection of a broad range of bacteria infecting hedgehogs and/or their associated arthropods. DNA of potential new Ehrlichia and Bartonella species have been detected respectively in ticks and fleas.